2014
DOI: 10.1073/pnas.1305499111
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt increases in Amazonian tree mortality due to drought–fire interactions

Abstract: Interactions between climate and land-use change may drive widespread degradation of Amazonian forests. High-intensity fires associated with extreme weather events could accelerate this degradation by abruptly increasing tree mortality, but this process remains poorly understood. Here we present, to our knowledge, the first field-based evidence of a tipping point in Amazon forests due to altered fire regimes. Based on results of a large-scale, longterm experiment with annual and triennial burn regimes (B1yr an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
710
3
30

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 648 publications
(798 citation statements)
references
References 42 publications
21
710
3
30
Order By: Relevance
“…observed in 2010 over regions in eastern Mato Grosso, south east, and central Pará, and this has been documented by Brando et al (2014).…”
Section: (The Geographic Distributions Are Illustrated Inmentioning
confidence: 82%
See 2 more Smart Citations
“…observed in 2010 over regions in eastern Mato Grosso, south east, and central Pará, and this has been documented by Brando et al (2014).…”
Section: (The Geographic Distributions Are Illustrated Inmentioning
confidence: 82%
“…The annual number of classified forest and maintenance fires have similar temporal pattern, with a correlation of 0.85. The greatest numbers of classified forest fires occurred in 2007 and 2010 and this was also noted by Morton et al (2013) for southern Amazonia and by Brando et al (2014) for eastern Mato Grosso, and was suggested as being related to the drier conditions in these years Brando et al 2014). The forest and deforestation fires have a less similar temporal pattern with a correlation of 0.59.…”
Section: Quantitative Assessmentmentioning
confidence: 88%
See 1 more Smart Citation
“…Tree mortality from heat and fire damage that year was more than four times that of a normal year 8 , especially along the forest edge, which the researchers burn every three years in a cycle emulating traditional Amazonian agricultural practices, says ecologist Paulo Monteiro Brando of Brazil's Amazon Environmental Research Institute in Brasília. In the Amazon, burning is the cheapest and most effective way for farmers to clear fields and give them a nutrient boost before planting crops, or rid them of ticks that plague livestock.…”
Section: Line Of Firementioning
confidence: 99%
“…Average dry season length (number of months with precipitation ≤100 mm) maps of Amazon basin (2B) adapted from Brando et al (2014). Estimated pattern of biomass and carbon accumulation in Amazonian forests: dense rainforest on nonflooding lowlands (A), dense rainforest on flooded lowland (B), semideciduous seasonal nonflooding forest (C), semideciduous seasonal flooding forest (D), seasonal forest savanna (E), and seasonal woodland savanna (F).…”
Section: Predictores Biofísicosmentioning
confidence: 99%